Tariff diversity and competition policy: Drivers for broadband adoption in the European Union - Mirjam R. J. Lange (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
While second-degree price discrimination is standard in commercial practice in many industries, consumer advocates and public interest groups have reacted with skepticism against tendencies to move away from flat rates and introduce greater tariff diversity. This paper provides an empirical analysis how the differentiation of broadband tariffs with respect to retail prices affects fixed broadband subscription using time-series data. The empirical analysis is based on a unique dataset of 10,200 retail broadband offers spanning the 2003-2011 period and including 23 EU member states. Results show that an increase in tariff diversity provides a significant impetus to broadband adoption, wherefore demands by some public interest groups to limit price discrimination in broadband markets should be viewed with some caution as reduced price discrimination may come at the cost of lower penetration rates.
Keywords: L86; L96; 330; Broadband demand; Tariff diversity; Price discrimination; Dynamic panel data analysis